The invasive bark beetle, Pagiocerus frontalis (Fabricius): as an emerging maize storage pest in Tanzania - Chidege, Maneno Y.; Venkataramana, Pavithravani B.; Ndakidemi, Patrick A. (Frontiers in Plant Science, 2026)
In Tanzania, smallholder farmers often sell maize immediately after harvest to avoid post-harvest losses caused by storage pests, a practice that exacerbates food insecurity. The invasive bark beetle Pagiocerus frontalis (Fabricius, 1801) (Coleoptera: Curculionidae), which infests maize and avocado seeds, was first detected in Tanzania in December 2018 in stored provitamin A yellow maize (CP 201). Host plant resistance represents a safe and sustainable strategy for managing storage insect pests. In this study, we evaluated the susceptibility of 27 maize varieties commonly cultivated in Tanzania. The varieties were assessed for grain damage, weight loss, progeny production, time to progeny emergence, and adult insect mortality. Significant differences were observed in grain damage and adult mortality, whereas no significant differences were detected in grain weight loss, progeny number, or time to progeny emergence. These findings demonstrate that P. frontalis can inflict substantial damage across all major maize varieties in Tanzania. This study provides the first evidence of varietal susceptibility to this invasive pest and establishes a foundation for developing integrated pest management strategies aimed at safeguarding maize production and enhancing food security in Tanzania and across Africa.